Penguatan Kompetensi Guru melalui Deep Learning dan Karakter Asta Cita (Kolaborasi, Kepemimpinan, dan Daya Saing) sebagai Fondasi Pendidikan Berkualitas Menuju Indonesia Emas 2045 - Putera, Rafhi Febryan; Ladiva, Hasmai Bungsu; Indrawadi, Junaidi; Safitri, Sanseni; Kurniawan, Cecep (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity was motivated by the importance of improving the competency of elementary school teachers to face the challenges of 21st-century education. The main objective of the activity was to improve teachers' understanding of the concept of deep learning while integrating the Asta Cita character values (collaboration, leadership, and competitiveness) as the foundation of quality education towards a Golden Indonesia 2045. The program was implemented by the Merak Study Group (Kombel) in IV Koto District, Agam Regency, involving teachers, academics, and students. The activity methods included preparation, outreach and training, implementation assistance, evaluation, and follow-up. The results of the activity demonstrated an increase in teachers' understanding of deep learning, their ability to develop innovative teaching tools, and the development of products in the form of modules and digital teaching tools. This activity made a significant contribution to strengthening teacher competency and collaboration between schools, thus playing a strategic role in achieving quality education.